2008
DOI: 10.1158/0008-5472.can-08-0479
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cytokinesis after X-Irradiation in Tumor Cells that Override the G2 DNA Damage Checkpoint

Abstract: X-irradiation-induced DNA damage perturbs the G 1 , S, and G 2 phases of the cell cycle. The behavior of cells after they have experienced a DNA damage checkpoint delay is poorly characterized. We therefore examined the fates of irradiated tumor cells that have overcome a prolonged G 2 checkpoint delay. Most irradiated cells progressed through mitosis without significant delay, but failed to complete cytokinesis as they remained tethered to each other at the midbody. We observed that the movement of centrioles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Nevertheless, the origin of these DNA bridges is still unclear; they may result from various defects, including persistent DNA double-strand breaks (36). Interestingly, X-irradiation, a common cause of double-strand breaks, has been reported to induce chromatin bridges and trigger binucleation (37). It is therefore tempting to speculate that unrepaired DNA double-strand breaks resulting from collapsed replication forks may be the source of elevated chromatin bridges in FA pathway-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the origin of these DNA bridges is still unclear; they may result from various defects, including persistent DNA double-strand breaks (36). Interestingly, X-irradiation, a common cause of double-strand breaks, has been reported to induce chromatin bridges and trigger binucleation (37). It is therefore tempting to speculate that unrepaired DNA double-strand breaks resulting from collapsed replication forks may be the source of elevated chromatin bridges in FA pathway-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Stained cells were mounted in Vectashield (Vector Laboratories) or mounting medium (Sigma). Images were taken with a Zeiss LSM510 (confocal: 40ϫ objective), Zeiss Axiovert 200 M (63ϫ objective), or Nikon Eclipse E800 (10,20, and 65ϫ objective) microscope with the Axio Vision 4.6.3 or NIS elements BR3.0 software program.…”
Section: Methodsmentioning
confidence: 99%
“…Such failure of proper mitotic progression is associated with disruption of genomic integrity. Multinucleated cells have been observed following DNA damage caused by X-irradiation of HeLa cells (14,20,57) or after depletion of proteins that play a part in chromosome segregation and DNA repair (6,11,13,26,27,57), including DNA-PK (9,11,27,57). Repair of DSBs, essential for the maintenance of genome integrity, can occur through homologous recombination or nonhomologous end joining (NHEJ).…”
mentioning
confidence: 99%
“…Other authors, however, have found more antioxidant molecules in fibroblasts than in keratinocytes. Yohn et al (1991), using cells from different donors, found increased GSH-Px, SOD and catalase in fibroblasts compared to keratinocytes, and in keratinocytes compared to melanocytes (Huang et al, 2008).…”
Section: Resultsmentioning
confidence: 97%